The Role of Islamic and Conventional Microfinance in Tackling Financial Exclusion in Bangladesh, Nigeria, and Uganda - Tawfik Azrak; Muzamil Edema (Shirkah: Journal of Economics and Business, 2022)
There has been to pertinent study considering the growth of Islamic and conventional microfinance institutions as an antecedent of financial inclusion in Bangladesh, Nigeria, and Uganda in a single study. Adults who are financially excluded make up sizable numbers in Bangladesh, Nigeria, and Uganda, the three OIC countries. Financial exclusion has been addressed through the establishment of microfinance institutions. This study attempts to review the contribution of Islamic and conventional microfinance institutions established in these countries in tackling financial exclusion. The study used the data from the Global Findex Database of the World Bank and IMF Financial Access Survey to draw a comparative image of financial access among the countries. The evidence indicated that there are significant financial gaps across the countries and hence a huge opportunity for Islamic microfinance with its vast range of financial products could be implemented to spur economic growth and tackle financial exclusion. Policymakers can use the study's findings to entice and build new microfinance institutions with broadly inclusive products for all populations of these countries.